Perlindungan Hukum Klaim Asuransi Terhadap Kecelakaan Pesawat Sukhoi - Muhammad Wafi Hamdani; Makhrus Sholeh; Sumriyah Sumriyah (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
This journal was made the author with the aim to know how legal protection over insurance claims to passenger aircraft in Sukhoi Super Jet 100 aircraft crash occurred onIn 2012 last. In Sukhii Superjet 100 plane crash 100 raises questions related to how legal protection against Suchoi aircraft passengers and how recognition of Sukhoi's passenger insurance claims. The question arises because it is interesting to assess whether the SUKHOI aircraft passengers can claim insurance against accidents resulting in deaths to all passengers of Sukhoi aircraft totaling 47. BecauseIn the case of a carrier entrepreneurian registered registration of aircraft accidents as set out in the Ministerial Regulation No. 77 of 2011 on the responsibility of air transport in the chapter of III Article 16 and 17.Based on the law the Sukhoi does not register the mandatory crash crashThis is becauseThe passenger is not a commercial passengerAl that has airline ticketsand they are the invited guest for Joy FlightThe plane. Because of itThat, it is necessary to know clearly whether the victim of the Sukhoi Plane AccidentThis SuperJet 100 is entitled to becompensationor insurance claimsIf viewed from Law no. 1The year 2009and other legislation related.